Case reportCan biologic treatment induce cutaneous focal mucinosis? - Lesiak, Aleksandra; Włodarczyk, Marcin; Sobolewska, Aleksandra; Sieniawska, Joanna; Rogowski-Tylman, Michał; Sysa-Jedrzejowska, Anna; Olejniczak-Staruch, Irmina; Narbutt, Joanna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Skin mucinosis is a rare skin disease which clinically manifests as firm papules and waxy nodules. We report a case of a 66-year-old female psoriatic patient who developed skin mucinosis during biological therapy. Because of a previous lack of response to the local and conventional systemic treatment of psoriasis, the patient received biological therapy (infliximab from June 2008 to May 2009 – initial clinical improvement and loss of treatment effectiveness in the 36th week of the therapy; adalimumab from June 2009 to January 2010 – lack effectiveness; ustekinumab from March 2012 to the present). Throughout 2 months we observed a manifestation of the skin mucinosis as well-demarcated, yellow and brown, papulo-nodular lesions of 5–10 mm in diameter, localized on the back. Histopathological examination with alcian blue staining demonstrated mucin deposits in the dermis. On the basis of clinical and histopathological findings, the diagnosis of cutaneous focal mucinosis was established. We present the case because of the extremely rare occurrence of the disease. Scarce literature and data suggest that there is an association between focal mucinosis and thyroid dysfunction, as well as possible adverse effects of biological therapy with TNF-α antagonists.